Cable-Driven Underactuated Flexible Gripper for Brown Mushroom Picking - Haonan Shi; Gaoming Xu; Yixuan Xie; Wei Lu; Qishuo Ding; Xinxin Chen (Agriculture)
Brown mushrooms are widely consumed globally due to their low calorie content, high nutritional value, and suitability for periodic growth in industrial mushroom houses, offering significant commercial value. Most robotic grippers pick mushrooms based on precise force control, which requires a high-precision force sensor, increasing production costs and potential failure rates. This study presents a fully soft gripper, as the body made of silicon rubber and driven by cable. Its inherent softness, offering a more natural solution for safely picking mushrooms by relying only on simple position control of the servo. Finite element analysis was employed to optimize the cable-driven displacement. Additionally, the gripper can measure mushroom diameters during picking using rough thin-film force sensors and bending sensors attached to the fingers, based on mathematical derivation. Field experiments were conducted with the proposed gripper mounted on a homemade mushroom-harvesting robot to pick medium-sized and large-sized mushrooms. The results demonstrated non-destructive harvesting, an average measurement accuracy of 96.6% for medium mushrooms and 96.1% for large mushrooms, and an average harvesting time of 7.5 s per mushroom. Compared to force-controlled grippers, the proposed cable-driven gripper features a simpler structural design and more efficient control logic, making it highly suitable for industrial applications.